Faecal microbiota transplantation for refractory Clostridiumdifficile infection. Issue 11 (27th November 2019) - Tamilarasan, Aravind Gokul; Irving, Peter; Meadows, Christopher IS; Goldenberg, Simon
Abstract : Faecal microbiota transplantation (FMT) has become a part of the treatment algorithm for Clostridium difficile infection (CDI), particularly for recurrent infections when antibiotics have diminishing efficacy. Notably, despite a significant proportion of patients suffering from refractory disease, there is a general lack of evidence describing the use of FMT in this patient cohort. We present here a case of successful treatment of refractory CDI in a patient under critical care.